Peripheral proteomic changes after electroconvulsive seizures in a rodent model of non-response to chronic fluoxetine - Lebeau, Rodolphe H.; Mendez-David, Indira; Kucynski-Noyau, Laura; Henry, Céline; Attali, David; Plaze, Marion; Colle, Romain; Corruble, Emmanuelle; Gardier, Alain M.; Gaillard, Raphaël; Guilloux, Jean-Philippe; David, Denis J. (Frontiers in Pharmacology, 2022)
Major depressive disorder (MDD) is the psychiatric disorder with the highest prevalence in the world. Pharmacological antidepressant treatment (AD), such as selective serotonin reuptake inhibitors [SSRI, i.e. fluoxetine (Flx)] is the first line of treatment for MDD. Despite its efficacy, lack of AD response occurs in numerous patients characterizing Difficult-to-treat Depression. ElectroConvulsive Therapy (ECT) is a highly effective treatment inducing rapid improvement in depressive symptoms and high remission rates of ~50–63% in patients with pharmaco-resistant depression. Nevertheless, the need to develop reliable treatment response predictors to guide personalized AD strategies and supplement clinical observation is becoming a pressing clinical objective. Here, we propose to establish a proteomic peripheral biomarkers signature of ECT response in an anxio/depressive animal model of non-response to AD. Following determination of an emotionality score, using complementary behavioral analysis of anxiety/depression across three different tests (Elevated Plus Maze, Novelty Suppressed Feeding, Splash Test), we showed that a 4-week corticosterone treatment (35 μg/ml, Cort model) in C57BL/6JRj male mice induced an anxiety/depressive-like behavior. Then, chronic fluoxetine treatment (Flx, 18 mg/kg/day for 28 days in the drinking water) reduced corticosterone-induced increase in emotional behavior. A 50% decrease in emotionality score threshold before and after Flx, was used to separate Flx-responding mice (Flx-R, n=18), or Flx non-responder mice (Flx-NR, n=7). Then, Flx-NR mice received 7 sessions of electroconvulsive seizure (ECS, equivalent to ECT in humans) and blood was collected before and after ECS treatment. Chronic ECS normalized the elevated emotionality observed in Flx-NR mice. Then, proteins were extracted from peripheral blood mononuclear cells (PBMCs) and isolated for proteomic analysis using a high-resolution MS Orbitrap. The proteomic analysis revealed a signature of 33 peripheral proteins associated with response to ECS (7 down- and 26 upregulated). These proteins were previously associated with mental disorders and involved in regulating pathways which participate to the depressive disorder etiology. Future preclinical studies will be required to validate whether proteomic changes observed in PBMCs from Cort/FlxR mice mirror biological changes in brain tissues.